MODELING OF THERMOELECTRIC SYSTEM FOR LOCAL THERMAL EFFECTS ON HUMAN FOREARM ZONE - T. A. Ismailov; O. V. Evdulov; M. A. Hazamova; R. A.-M. Magomadov (Вестник Дагестанского государственного технического университета: Технические науки)
In this paper we consider a model of the thermoelectric system for the thermal effect on the human forearm. The model is implemented on the basis of numerical solution of differentialequations of heat conduction for bodies of complex configuration. Two-dimensional and onedimensional graphs of the temperature change in different zones of the object of exposure aregiven.